Early Postnatal Care: Exploring Primary Caregivers’ Experiences of Continuity of Care After Discharge at Selected Districts in Limpopo Province South Africa - Shirindza KJ; Malwela T; Maputle MS (Patient Preference and Adherence, 2022)
Katekani Joyce Shirindza, Thivhulawi Malwela, Maria Sonto Maputle University of Venda, Faculty of Health Sciences, Department of Advanced Nursing, Thohoyandou, South AfricaCorrespondence: Maria Sonto Maputle, University of Venda, Faculty of Health Sciences, Department of Advanced Nursing, Private Bag X 5050, Thohoyandou, South Africa, Tel +271 5 962 8125, Email sonto.maputle@univen.ac.zaBackground: Early postnatal discharge is perceived as a factor that contributes to possible maternal, neonatal complications and deaths during the first week of delivery. Continuing with provision of home-based postnatal care by the primary caregivers is crucial to prevent morbidity and mortality.Purpose: The purpose was to explore the experiences of primary caregivers of continuing with the provision of early postnatal care at home.Method: A qualitative research approach, which was explorative, descriptive, and contextual was conducted in the three selected districts of different ethnic groups at Limpopo Province in October 2019. A non-probability, purposive sampling was used to conveniently sample 20 primary caregivers of postnatal women. Data were collected during the first 2 weeks of delivery through in-depth individual semi-structured interviews until data saturation was reached. Data were analysed through a thematic analysis framework applying Tesch’s open coding method. The study was done in Limpopo district, South Africa.Findings: The findings revealed a theme, namely, knowledge and skills of providing community-based postnatal care and three sub-themes; early postnatal care to detect and prevent possible complications to the mother; general postnatal care, and early neonatal care to detect and prevent possible complications.Conclusion: Primary caregivers displayed acceptable indigenous skills and knowledge of providing early postnatal care. However, the skills of detecting potential danger signs were not adequately displayed. It was recommended that midwives need to create awareness to primary caregivers from the antenatal through postnatal care period. Community Health Workers to assist during immediate postnatal check-ups (mother and neonate) which is done within 72hours of delivery. The health education, counseling, and community-based awareness campaigns are to be done with a focus on the detection and prevention of possible complications to mother and baby.Keywords: early postpartum discharge, maternal and neonatal complications, postnatal care, primary caregivers